An introduction to CorelDRAW! for business users - Stewart, Kathleen. (Boyd and Fraser, 1994)
Introduction to CorelDraw! Artistic text. Enhancing artistic text. Working with Clip art. Transformations. Special effects. Lines and curves. The fill and outline tools. Paragraph text and print merge...